Tortura policial: más allá de “confesiones” para el sistema de justicia penal - Silva Forné, Carlos; Padilla Oñate, Sergio (El Colegio de México, 2022)
The analysis of torture by police officers in Mexico has focused on its relations with the criminal justice system. Using the National Survey of People Deprived of their Freedom survey, logit models were constructed to test two alternative explanations: rent extraction and punishment, also the tendencies among federal, state and municipal forces were compared. The results confirm the importance of develop explanations related to torture by police that transcend the legal perspective and account the complexity of the police work. Finally, we discuss the limits of the results and suggest new research routes.